2017
DOI: 10.1080/03079457.2017.1390208
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Ornithobacterium rhinotracheale to chicken embryo lung cells as a pathogenic mechanism

Abstract: Ornithobacterium rhinotracheale is a bacterium that causes respiratory disease in birds and it has been isolated in countries with a large poultry production, including Mexico. The pathogenicity mechanisms of this bacterium have not been completely elucidated yet. The capacity of the bacterium to adhere to epithelial cells of chicken in vitro has been evidenced, and since this bacterium has been isolated from the lungs and air sacs of several avian species, the aim of this study was to determine if this bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Currently, 18 ORT serotypes (A-R) have been reported, with no direct relationship with virulence. Due to the difficulty of the serotyping process, it has been suggested that there are new serotypes yet to be determined [2,3,21].…”
Section: Ornithobacterium Rhinotracheale (Ort)mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, 18 ORT serotypes (A-R) have been reported, with no direct relationship with virulence. Due to the difficulty of the serotyping process, it has been suggested that there are new serotypes yet to be determined [2,3,21].…”
Section: Ornithobacterium Rhinotracheale (Ort)mentioning
confidence: 99%
“…Cell viability studies have shown that ORT can adhere to chicken embryo lung cells after 3 h incubation, resulting in a diffuse growth pattern. There are appendages and hemagglutinins, which probably contributed to the adhesion, suggesting the presence of host cell receptors that recognize ORT adhesins [21].…”
Section: Clinical Signs and Pathological Lesionsmentioning
confidence: 99%
“…ORT infection is common in turkeys and chickens and can be transmitted horizontally and vertically. To date, 18 ORT serotypes (A–R) have been identified, but no direct relationship with virulence has been reported ( Zahra et al., 2013 ; De la Rosa-Ramos et al., 2018 ; Montes et al., 2018 ). Analysis of the rpoB gene has been used to distinguish similar strains ( Veiga et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium primarily infects the trachea, lungs, and air sacs, but can also manifest as a systemic disease [8,12]. The ORT bacterium is most commonly isolated from the trachea and lungs of naturally or experimentally infected birds [17][18][19]. In our study, the bacterium was not isolated from the respiratory system by the culture in the vaccinated groups in the DAC.…”
Section: Discussionmentioning
confidence: 52%